Effect of Tomato Juice Volume on Coagulation Time and Latex Weight - Dewi Putri Yuniarti; Hatina, Surya; Afriyani, Nidya (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2023)
Natural latex clumping takes longer than using chemicals. Another alternative is needed to coagulate the latex by adding acid from natural ingredients. Tomatoes (Lycopersicum esculentum Mill) have 29.32 mg of ascorbic acid and 0.54 g of citric acid every 100 grams, they have the potential to be used as a natural latex coagulator. The research method add tomato juice to fresh latex to break down the emulsion and form rubber lumps. After mixing, the weight of the latex is weighed. The constant variables are the latex volume of 10 ml, and the tomato juice volume of 5,10,20,30,40,50,60,70,80,90 and 100 ml respectively. The higher the volume of tomato juice, the faster it will clot. The best volume of tomato juice is 100 ml with a clumping time of 52 minutes. Increasing the volume of tomato juice increased the weight of latex to 13.1 grams and reduced the pH of latex to 4.9. Giving tomato juice every 5 ml accelerated clumping up to 360 minutes (6 hours) compared without tomato juice.